RESPON PEMERINTAH CINA TERHADAP KEBIJAKAN SEAFOOD IMPORT MONITORING PROGRAM (SIMP) AMERIKA SERIKAT - Kusumawati, Adinda; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aim to explain the trade protect imposed by the United States. Technical Barriers to Trade cause barriers to exports of fishery products for China. The discussion in this study is China's response to the Seafood Import Monitoring Program policy issued by the United States.This research uses data collection techniques using the Literature Study method. Protectionism theory by Friedrich List to analyze the response of the Chinese government in protecting fishery products in its country. The perspective used by the author is mercantilism which in trade countries must issue regulations to The results of this indicate that China's response as a fishery exporting country seeks to meet the requirements given by the United States and provide countermeasures in the form of making the same policy. China accepted the conditions given by the United States by improving its domestic policies and making additional rules by making the same policy.Keywords: Kebijakan, Perdagangan, Seafood, Regulasi Amerika Serikat